Study of properties of membranes based on carboxymethyl cellulose and chitosan - Вікторія Олексіївна Овсянкіна; Валерій Леонідович Демченко; Олександр Петрович Хохотва; Тамара Володимирівна Крисенко; Максим Володимирович Юрженко (Вісник Національного технічного університету України «Київський політехнічний інститут імені Ігоря Сікорського»: Серія «Хімічна інженерія, екологія та ресурсозбереження»)
Оne of the promising directions is the obtaining  of  biodegradable nanocomposite membranes, which allow to achieve a high level of purification and do not pollute the environment after their using. Anionic polyelectrolyte – Na-carboxymethyl cellulose with molecular weight Mw ~ 90000 and cationic polyelectrolyte – low molecular weight chitosan were used to create these membranes. Polymeric membranes were formed by mixing aqueous solutions of chitosan hydrochloride and Na-carboxymethylcellulose in different ratios. For study of the mechanical properties  of membranes based on natural polymers such as chitosan and Na-CMC, the membranes were tested by the AG-Xplus apparatus by breaking. It was established that the membranes based on chitosan and Na-CMC have high mechanical strength. They can withstand a pressure of more than 5 atmospheres without damage. This makes it suitable for using in various conditions, including industrial ones. A barometric device was used to test the effectiveness of the obtained membranes. The study was conducted at different pressures (3, 4, 5 atm). It was established that membranes based on polyelectrolyte complexes with a stoichiometric ratio of anionic and cationic polyelectrolytes were the most productive.